Neo-Modernism: A Vital Synthesis of Traditionalist and Modernist Islamic Thought in Indonesia - Greg Barton (Studia Islamika, 1995)
This paper is concerned with exploring the early stages of a new movement is Islamic thought in Indonesian society referred to by some as Islamic neo-modernism by focusing upon the lives and writings of the four seminal neo-modernist thinkers in Indonesia: Nurcholish Madjid, Djohan Effendi, Ahmad Wahib and Abdurrahman Wahid.Whilst the later work of these intellectuals, particularly Nurcholish and Abdurrahman, is reasonably well known the extend to which their current liberal, progressive thought reflects their convictions of two, or more, decades ago is not well understood. An examination of their writing from the 1970s reveals a striking consistency in their thought and suggest that their ISlamic liberalism is deeply rooted.DOI: 10.15408/sdi.v2i3.827